Assignment and frequency measurement of rotational transitions of (CD3OH)-C-13 by intracavity laser Stark spectroscopy - Moraes, João Carlos Silos [UNESP]; Pereira, D.; Carelli, G.; Moretti, A.; Strumia, F. (Elsevier B.V., 1996)
We present the results of an intracavity Stark spectroscopy experiment on the fundamental state of (CD3OH)-C-13. We use an optically pumped hybrid waveguide FIR laser, CH2F2 as active molecule, and (CD3OH)-C-13 as absorbent molecule. No Brewster window is needed to separate the lasing gas from the absorbing deuterated methanol. An absorption line is assigned as E(l) symmetry (n, K, J): (1,4,18) --> (1,5,18) and its frequency is measured as 63.08631 cm(-1) with a precision of a few parts in 10(7); two more absorptions are reported and a tentative assignment for one of them.